DAMPAK MEDIASI EARNINGS MANAGEMENT PADA PENGARUH TOURNAMENT INCENTIVES TERHADAP KEMUNGKINAN TERJADINYA FRAUD DALAM LAPORAN KEUANGAN - Hidayatul Khusnah (UNUSA Press, 2020)
This study aims to investigate the effect of tournament incentives on earnings management and fraud, as well as the mediating impact of earnings management on the effect of tournament incentives on fraud. This research was conducted in manufacturing companies listed on the Indonesia Stock Exchange (IDX) which publish annual financial reports for six consecutive years, starting from 2014 to 2019. The data in this study were obtained from the official website of the Indonesia Stock Exchange (www. idx.co.id), the website of each company, www.ahamok.com. The data analysis technique in this study used SEM-PLS analysis using the WarpPLS 5.0 software. The results of this study indicate that tournament incentives have a positive effect on the possibility of fraud in financial reports and earnings management. This study also found a positive effect of earnings management on the possibility of fraud in financial statements. Finally, this study did not find a mediating effect of earnings management on the effect of tournament incentives on the possibility of fraud in the financial statements.